Desenvolvimento do campo retrodifusor seletivo de alumínio e boro em células solares de silício - Crestani, Thais (2016)
The typical solar cells of the industry are fabricated in p-type crystalline silicon wafers and have a pn junction at one side and, on the other side, the back surface field (BSF). The objective of this work is to develop solar cells with aluminum and boron selective back surface field to enable the passivation on the rear face with an industrial process. Czochralski p-type silicon wafers of solar grade quality were used. The boron diffusion was performed on the whole back side of the silicon wafers and the aluminum was screen-printed to form the selective back surface field under the metal grid. The boron diffusion temperature and time, the firing temperature of the metal pastes, the percentage of the rear area covered with aluminum and the passivation with SiO2 were evaluated in the electrical parameters. The best boron diffusion temperature was 970 ° C for 20 minutes and firing temperature of the metal pastes was 870 ° C. The solar cell with the highest efficiency were obtained for a rear metal grid with 14 % of the area covered by aluminum. The passivation by SiO2 on both surfaces increased the minority charge carrier diffusion length from 490 μm to 665 μm. Consequently, the passivation increased the efficiency from 15.6 % to 16.1 %, as a result of an increasing of the fill factor and the open circuit voltage. The passivation also increased the internal quantum efficiency in the range of violet/blue wavelengths as well as in the near infrared region.